Operative Times in Primary Total Knee Arthroplasty: Can We Predict the Future Based on Contemporary Nationwide Data - Sultan, Assem A.; Samuel, Linsen T.; Karnuta, Jaret M.; Acuña, Alexander J.; Mahmood, Mustafa; Kamath, Atul F. (The Journal of Knee Surgery, 2019)
Recently, the Centers for Medicare & Medicaid Services announced its decision to review “potentially misvalued” Current Procedural Terminology (CPT) codes, including those for primary total knee arthroplasty (TKA). CPT 27447 is being reevaluated to determine contemporary relative value units for work value, with operative time considered a primary factor in this revaluation. Despite broader indications for TKA, including extension of the procedure to more complex patient populations, it is unknown whether operative times may remain stable in the future. Therefore, the purpose of this study was to specifically evaluate future trends in TKA operative times across a large sample from a national database. The American College of Surgeons National Surgical Quality Improvement Project database was queried from January 1, 2008 to December 31, 2017 to identify 286,816 TKAs using the CPT code 27447. Our final analysis included 140,890 TKAs. Autoregressive integrated moving average forecasting models were built to predict 2- and 10-year operative times. While operative times were significantly different between American Society of Anesthesiologists (ASA) classes 1 and 2 (p = 0.035), there were not enough patients in ASA class 1 to perform rigorous inference. Additionally, operative times were not significantly different between ASA classes 3 and the combined ASA classes 4 and 5 cohort (p = 0.95). Therefore, we were only able to perform forecasts for ASA classes 2 and 3. Operative time was found to be nonstationary for both ASA class 2 (p = 0.08269) and class 3 (p = 0.2385). As a whole, the projection models indicated that operative time will remain within 2 minutes of the present operative time, up to the year 2027. Our projections indicate that operative times will remain stable over the next decade. This suggests that there is a lack of evidence for reducing the valuation of CPT code 27477 based on intraservice time for TKA. Further study should examine operative time trends in the setting of evolving alternative payment models, increasing patient complexity, and governmental restrictions.
Keywords: operative time; total knee arthroplasty (TKA); trends; reimbursement; Current Procedural Terminology (CPT); autoregressive integrated moving average (ARIMA)